Proceedings of the 4th International Symposium on Information, Computer, and Communications Security 2009
DOI: 10.1145/1533057.1533069
|View full text |Cite
|
Sign up to set email alerts
|

On the feasibility of launching the man-in-the-middle attacks on VoIP from remote attackers

Abstract: The man-in-the-middle (MITM) attack has been shown to be one of the most serious threats to the security and trust of existing VoIP protocols and systems. For example, the MITM who is in the VoIP signaling and/or media path can easily wiretap, divert and even hijack selected VoIP calls by tempering with the VoIP signaling and/or media traffic. Since all previously identified MITM attacks on VoIP require the adversary initially in the VoIP signaling and/or media path, there is a common belief that it is infeasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…Zhang et al [74] show that, by exploiting DNS and VoIP implementation vulnerabilities, it is possible for attackers to perform man-in-the-middle attacks even when they are not on the direct communication path of the parties involved. They demonstrate their attack against Vonage, requiring that the attacker only knows the phone number and the IP address of the target phone.…”
Section: D) Captchas and Puzzles (4 Items)mentioning
confidence: 99%
“…Zhang et al [74] show that, by exploiting DNS and VoIP implementation vulnerabilities, it is possible for attackers to perform man-in-the-middle attacks even when they are not on the direct communication path of the parties involved. They demonstrate their attack against Vonage, requiring that the attacker only knows the phone number and the IP address of the target phone.…”
Section: D) Captchas and Puzzles (4 Items)mentioning
confidence: 99%
“…Wang et al [24] investigated the trust of several leading VoIP services (e.g., Vonage, AT&T) and showed that their VoIP calls can be transparently diverted and redirected-leading to voice pharming attacks on the VoIP users. It has been further detailed [26] that these call diversion attacks can be launched by a remote attacker who is not initially in the path of VoIP traffic of the target.…”
Section: Related Workmentioning
confidence: 99%
“…The authors argue for the need for TLS or IPsec protection of the signaling. Zhang et al [62] show that, by exploiting DNS and VoIP implementation vulnerabilities, it is possible for attackers to perform man-in-the-middle attacks even when they are not on the direct communication path of the parties involved. They demonstrate their attack against Vonage, requiring that the attacker only knows the phone number and the IP address of the target phone.…”
Section: Addressing Social Threats (49 Items)mentioning
confidence: 99%